Socio-Economic Implications of Gender Earning Differentials :Education Sector in Orissa - BEDABATI MOHANTY, TRILOCHAN TRIPATHY (Economic and Political Weekly May 21, 2005, 2005)
This paper seeks to throw light on earning differences that exist between males and females working in the education sector and the reasons for these differentials. The extent of differential attributed to human capital endowment and the extent attributed to pure gender discrimination have been estimated through decomposition analysis. The paper also looks at the status of women in the family and the possible link between earning and the status of women.